2015
DOI: 10.1136/bmjopen-2015-007786
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characteristics, management and 1-year outcomes of patients with acute coronary syndrome in Iran: the Iranian Project for Assessment of Coronary Events 2 (IPACE2)

Abstract: ObjectivesTo assess contemporary data on characteristics, management and 1-year postdischarge outcomes in Iranian patients hospitalised with acute coronary syndrome (ACS).Setting11 tertiary care hospitals in 5 major cities in the Islamic Republic of Iran.ParticipantsPatients aged ≥20 and ≤80 years discharged alive with confirmed diagnosis of ACS including ST-segment elevation myocardial infarction (STEMI), non-STEMI (NSTEMI) and high-risk unstable angina (HR-UA).Primary and secondary outcome measuresPatients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
1
23
2
1
Order By: Relevance
“…Another reason could also be due to delayed admission time to the hospital, where the mean time of presentation was around four days. In contrary, the finding of the present study was lower than reports from Iran 17.3% [33], South Africa 53%(31), Kenya 38% [35], Greece 27.0% [36] and Ethiopia 65.3% [37]. Possibly, the inconsistency is due to wide accessibility of PCI service in these areas.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Another reason could also be due to delayed admission time to the hospital, where the mean time of presentation was around four days. In contrary, the finding of the present study was lower than reports from Iran 17.3% [33], South Africa 53%(31), Kenya 38% [35], Greece 27.0% [36] and Ethiopia 65.3% [37]. Possibly, the inconsistency is due to wide accessibility of PCI service in these areas.…”
Section: Discussioncontrasting
confidence: 96%
“…Another plausible reason could be lack of adequate accessibility and affordability of the medication in relation to the socio-economic status of the patients. Our study revealed a lower percentage of thrombolytic use compared to studies from Kenya 79.5% [30], South Africa 18% [31], sub-Saharan countries 44.4% [32] and Iran 46.3% [33]. This could be due to better availability and accessibility of thrombolytic medications in Kenya, South Africa and similarly in Iran too.…”
Section: Discussioncontrasting
confidence: 60%
“…The methodological quality assessment indicated that the quality of 36 included studies was excellent or good [ 12 , 13 , 19 , 23 - 25 , 27 - 38 , 40 , 41 , 44 , 45 , 47 , 48 , 50 - 60 , 64 ], whereas the quality of seven studies was scored moderate [ 26 , 42 , 46 , 49 , 61 , 62 , 63 ] and two studies were scored poor [ 39 , 43 ] (Table 1 )). Most studies lacked a detailed description of primary and secondary outcomes and related measurement sources, the handling of missing data, and/or the adjustment for confounders in multivariable analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Kassaian et al (2015), in Tehran city, it was reported as 30 min. [ 21 ] Moreover, the time interval between visit by the doctor to leave the emergency ward was reported as 51 min. [ 22 ] These results were not consistent with those of the present study as the time interval for leaving the emergency ward was 76 min.…”
Section: Discussionmentioning
confidence: 99%